1991
DOI: 10.1093/clinchem/37.10.1781
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of plasma parathyrin-related peptide: three region-specific radioimmunoassays and a two-site immunoradiometric assay compared

Abstract: We measured parathyrin (parathyroid hormone)-related peptide (PTHRP) in plasma by three region-specific RIAs and compared them with an established two-site immunoradiometric assay (IRMA) of PTHRP1-86 in samples from control subjects and from patients with primary hyperparathyroidism (PH) and humoral hypercalcemia of malignancy (HHM). The two direct RIAs of PTHRP1-34 and PTHRP37-67 were specific for regions 9-18 and 52-61, respectively. In the extraction RIA of PTHRP1-34 we used an affinity gel containing a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This is comparable with recent results of other assays against different sequences ofPTHrP. With few exceptions (Grill et al, 1990), measuring amino terminal PTHrP in plasma was not possible by direct RIA and required laborious preceding extraction steps, such as immunoaffinity chromatography (Budayr et al, 1989;Ratcliffe et al, 1991b) or C-2 or C-18 extraction cartridges (Kao et af., 1990). With these methods, Budayr et al (1989) found elevated levels in 33 of 48 (69%) patients with a solid tumour and hypercalcaemia, and Kao et al (1990) in 12 of 25 patients (48%).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is comparable with recent results of other assays against different sequences ofPTHrP. With few exceptions (Grill et al, 1990), measuring amino terminal PTHrP in plasma was not possible by direct RIA and required laborious preceding extraction steps, such as immunoaffinity chromatography (Budayr et al, 1989;Ratcliffe et al, 1991b) or C-2 or C-18 extraction cartridges (Kao et af., 1990). With these methods, Budayr et al (1989) found elevated levels in 33 of 48 (69%) patients with a solid tumour and hypercalcaemia, and Kao et al (1990) in 12 of 25 patients (48%).…”
Section: Discussionsupporting
confidence: 87%
“…Very recently, Ratcliffe et al, have developed an RIA against PTHrP(37-67). The antiserum ofqhis assay was thought to recognize the region spanning residues 52-61 and was used successfully in a twosite assay (Ratcliffe et al, 1991b). The RIA against PTHrP(37-67), however, detected much higher concentrations of PTHrP in normals (mean: 320 pmol/l) than our RIA, although the antiserum was directed against a nearby epitope.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The plasma levels of PTHrP(1-34) were measured with an in-house radioimmunoassay using an antiserum raised in rabbits to hPTHrP(1-34) which is specific for the 9-18 region. The validation of this assay is described by Ratcliffe et al (1991).…”
Section: Analysesmentioning
confidence: 99%